Desenvolvimento de metodologia de indicador da qualidade socioambiental urbana (IQSAU): aplicação em cidades do Paraná - Pereira, Máriam Trierveiler (2011)
World population growth since the Industrial Revolution and it has caused serious urban social, economic and environmental problems. Thus, the objective of the study was to develop an Urban Socio-Environmental Quality Indicator (IQSAU). It can be used by local governments and development agencies to devise strategies for urban planning in accordance with the needs of its citizens, giving them satisfactory living conditions and without excessive pressure on environmental systems. The indicator considered the socioeconomic status (education, health, public safety, employability and income, culture, art and sport); infrastructure and services status (mobility and accessibility, sanitation, communication and expression); environmental status (water quality, air quality, soil quality, green areas) and climate status (climate quality). This paper has presented an unprecedented contribution, because it considered various issues of social and urban environment, including a climate indicator, which had not been incorporated into the known indicators. Thus, they were aggregated information that characterize urban sustainable development, emphasizing the environmental sphere as being responsible for the quality of life. The main contribution was the diagnosis made at 16 largest cities in Parana. This work also proposed that some databases were created for public consultation on free and online form, so that other research in this area can be made. Clearly, it was noted that cities in the metropolitan region of Curitiba had poor results for the Human Indicators. It happens because the metropolis offers socio-economic conditions and infrastructure that are enjoyed by people from neighboring towns.